Comparative Analysis of Rural Health Demographics in 2 East African Communities During Medical Camps: Volunteers’ Perspectives’ - Adekunle Olowu (21363203) (2021)
Aims and Objectives To compare of basic health and social demographics observed during 4-day medical camps in 2 rural communities in Zambia and Malawi to determine any significant differences or similarities. Method About 12 and 10 local and international volunteers at medical camps (at a temporary rural health post or community hall) in rural Zambia and Malawi respectively treated 488 patients in total, with basic health and social demographic data collected and results analyzed. Results The mean age of patients seen in Malawi and Zambia were 34.5 and 38.9 years respectively, with 39% and 40% of patients in Malawi and Zambia respectively being within the 18 to 44 years age group, and mostly females (59.7% in Malawi and 65.7% in Zambia). Most were non-infectious diseases (97.3% in Zambia, 95% in Malawi), mostly musculoskeletal (17.0% in Malawi and 30.5% in Zambia), while medications prescribed were mostly analgesics (35.7% in Malawi and 29.9% in Zambia). Only a small proportion of patients were referred to local secondary facilities or district hospitals, 51 (28.7%) in Malawi and 59 (19.9%) in Zambia respectively. Chi square test shows a significant difference (P < .001) in diseases in both countries, but there was no statistically significant difference between the mean age of patients seen in both countries, using the independent t-test (P = .365). Conclusion This study highlights statistically significant demographic differences between the 2 communities and possible reasons for these, and how volunteers’ roles in rural healthcare in the East African communities could be further evaluated. Other Information Published in: Journal of Primary Care & Community Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/21501327211035095